Evaluating toxicity of heavy fuel oil fractions using complementary modeling and biomimetic extraction methods. (1st August 2014) - Redman, Aaron D.; Parkerton, Thomas F.; Letinski, Daniel J.; Manning, Ryan G.; Adams, Julie E.; Hodson, Peter V.
Abstract The toxicity of chemically dispersed heavy fuel oil (HFO) and 3 distillate fractions to rainbow trout (Oncorhynchus mykiss) embryos was evaluated using the PETROTOX model and a biomimetic extraction technique that involved passive sampling of oil‐contaminated test media with solid‐phase microextraction (SPME) fibers. Test solutions for toxicity testing were generated using a combination of dispersant and high‐energy mixing. The resulting water accommodated fractions (WAF) provided complex exposure regimens that included both dissolved hydrocarbons and oil droplets. The toxicity of the various fractions differed by approximately 3 orders of magnitude when expressed on the basis of WAF dilution. Using detailed compositional data, the PETROTOX model predicted the speciation of hydrocarbons between dissolved and oil droplet phases and explained observed toxicity based on computed dissolved phase toxic units (TUs). A key finding from model calculations was that dissolved hydrocarbon exposures and associated TUs were a nonlinear function of WAF dilution, because dissolved hydrocarbons were largely controlled by the dissolution of oil droplets that were transferred in WAF dilutions. Hence, oil droplets served to "buffer" dissolved concentrations in WAF dilutions at loadings greater than 1 mg/L, resulting in higher dissolved concentrations and TUs than expected based on dilution. The TUs computed at each WAF dilution explained the observed toxicity among the HFO and fractions to within a factor of 3. Dissolved material measured by SPME showed a consistent relationship with model‐predicted TUs, confirming the utility of this approach for providing an integrated measure of exposure to bioavailable hydrocarbons. These 2 approaches provide complementary tools for better defining bioavailability of complex petroleum substance. Environ Toxicol Chem 2014; 33:2094–2104. © 2014 SETAC